'A balancing act'. Living with severe chronic obstructive pulmonary disease in Southern New Zealand: a qualitative study - Tim Stokes; Simon Donlevy; Debbie Hannah; Jo Baxter; Jack Dummer; Kathryn McAuley; Anna Tiatia Fa'atoese Latu; Fiona Doolan-Noble; Emma Tumilty (CSIRO Publishing, 2020)
ABSTRACT INTRODUCTIONChronic obstructive pulmonary disease (COPD) is a common chronic condition managed in primary care. AIMTo understand how patients with severe COPD living in the Southern Health Region (Otago and Southland) experience and cope with the condition. METHODSSemi-structured interviews were undertaken with 23 patients with severe COPD (defined using the 2013 GOLD classification). A thematic analysis was conducted. RESULTSPatients' accounts of living with severe COPD revealed four themes: loss, adaptation, isolation and social support. All participants discussed their sense of loss in coming to terms with having COPD and the ongoing restrictions or changes that were associated with breathlessness and fatigue. These losses required adaptation in daily living. Some patients struggled to adjust to new limitations and needed to rely on others for support. Others found ways to adapt their surroundings or ways of doing things while trying to maintain the same activities. Isolation was described in two ways - direct (no longer being able to easily socialize because activities often caused breathlessness) and indirect (the feeling of being isolated from others because they do not understand what it is like to live with COPD). Social support, including support provided by group-based pulmonary rehabilitation, helped to address the problems of social isolation. DISCUSSIONLiving with severe COPD is a 'balancing act' between insecurity (loss and isolation) and resilience (adaptation and social support). Health-care providers need to be proactive in identifying and managing patients' unmet health needs and promote activities that reduce social isolation.